Proton conduction composite membrane for flow battery and preparation method of proton conduction composite membrane
The proton-conducting composite film for flow batteries was prepared by combining polyvinylidene fluoride and polybenzimidazole, which solved the problems of large resistance and low conductivity of the existing membrane, and achieved higher acid resistance and temperature resistance. and battery efficiency.
Patent Information
- Application Number
- CN202411523461.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
The existing proton conduction composite membranes have problems such as large resistance, low proton conduction current efficiency and poor solubility in flow batteries, which are difficult to meet the demands of flow batteries for acid resistance, temperature resistance and high conductivity.
Using a composite process, polyvinylidene fluoride and polybenzimidazole are combined, and a proton-conducting composite membrane is prepared through casting formation and oven heating steps to optimize the pore structure and mechanical strength of the membrane.
The acid resistance, temperature resistance and mechanical strength of the composite film are improved, the resistance value and pore size of the film are reduced, and the coulomb efficiency, energy efficiency and stable operating life of the flow battery are significantly improved.
Smart Images

Figure CN119447393A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to a proton conducting composite membrane for liquid flow batteries and a preparation method thereof. Background Art
[0002] With the limited use of non-renewable energy such as coal, oil, and natural gas, and the increasingly prominent problems of corresponding emissions and environmental pollution, how to reasonably and efficiently use renewable energy has become the focus of attention. For example, renewable energy such as wind energy and solar energy are affected by harsh conditions such as seasons, weather, and geographical factors, and have obvious instability and discontinuity. The power generated fluctuates greatly, which in turn has a great impact on the power grid. Therefore, with the rapid rise of renewable energy such as wind energy and solar energy and the smart grid industry, the development of energy storage technology used in conjunction with them has become the key.
[0003] In the flow battery, only ions of different valence states achieve the purpose of charge and discharge cycle through valence rise and fall, without other phase changes, so the battery has a long service life, good charge and discharge performance, zero emission and no pollution, and the system can be fully automatically closed and very stable and safe. The battery has a long service life, good charge and discharge performance, and can be deeply discharged without damaging the battery. The flow battery has a large degree of freedom in site selection, and most of the battery components are cheap carbon materials. The battery energy efficiency can reach 75%-85%, which has attracted widespread attention.
[0004] The proton conductive composite membrane is one of the core components of the flow battery. It is used to isolate the positive and negative electrolytes when flowing through the battery stack, to prevent the penetration of ions of different valence states from causing self-discharge and capacity loss, and to allow proton migration to ensure the electrochemical reaction. The performance and structure of the proton conductive composite membrane determine the efficiency, stability and life of the flow battery. The proton conductive composite membrane required for the flow battery should have the following characteristics: ① Low ion interpenetration rate, small cross contamination, reduced battery self-discharge, and improved energy efficiency. ② High proton permeability, low membrane resistance, and improved voltage efficiency. ③ It has a certain mechanical strength, is resistant to chemical corrosion and electrochemical oxidation, and ensures a long cycle life. ④ The water penetration is small during battery charging and discharging, maintaining the water balance of the positive and negative electrolytes.
[0005] Polyvinylidene fluoride (PVDF) is a highly non-reactive thermoplastic fluorinated polymer with excellent properties such as anti-aging, chemical resistance, weather resistance, and UV radiation resistance. It is currently one of the main raw materials for preparing porous membranes. However, PVDF membranes have the disadvantages of high thickness, high resistance, and high active material transmittance.
[0006] Polybenzimidazole (PBI) is a class of fully aromatic compounds with excellent properties such as high thermal stability, mechanical stability, flame retardancy, etc. It is considered to be the most suitable exchange membrane material to replace the traditional Nafion membrane. However, PBI also has shortcomings as a proton exchange membrane, mainly due to its obvious disadvantages such as large resistance, low proton conductivity, low current efficiency and poor solubility.
[0007] There is an urgent need for a porous proton conducting composite membrane with strong acid resistance, wide temperature resistance, high conductivity and strong ion selectivity. Summary of the invention
[0008] In view of the above problems, the present invention provides a proton conducting composite membrane for a liquid flow battery and a preparation method thereof.
[0009] The method for preparing a proton conducting composite membrane for a flow battery provided by the present invention comprises the following steps:
[0010] S1, dissolving polyvinylidene fluoride and a first modifying additive in a first organic solvent, and performing a first stirring to obtain a first casting solution; dissolving polybenzimidazole and a second modifying additive in a second organic solvent, and performing a second stirring to obtain a second casting solution;
[0011] S2, coating the first casting liquid on a flat support surface to form a first thin layer by casting, performing a first oven heating until the first thin layer is completely dried to obtain a base film, and then coating the second casting liquid on the surface of the base film to form a second thin layer by casting;
[0012] S3, heating the membrane structure obtained in step S2 in an oven for a second time until the second thin layer is completely dry, thereby preparing a proton conducting composite membrane.
[0013] further,
[0014] In the step S1, the mass percentage content of the polyvinylidene fluoride in the first casting solution is in the range of 10wt%-20wt%;
[0015] The molecular weight of the polyvinylidene fluoride is 500,000-1,000,000.
[0016] further,
[0017] The first modifying additive is zirconium oxide and tert-butyl hydroquinone;
[0018] The second modification additive is cerium oxide and tert-butyl hydroquinone;
[0019] In the first casting solution, the mass percentage content of zirconium oxide is in the range of 3wt%-7wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%;
[0020] In the second casting solution, the mass percentage content of cerium oxide is in the range of 0.05wt%-0.15wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%.
[0021] further,
[0022] The first organic solvent is dimethyl sulfoxide;
[0023] The second solvent is N,N-dimethylacetamide, N,N-dimethylformamide, or N-methylpyrrolidone.
[0024] further,
[0025] The mass percentage content of the polybenzimidazole is 1wt%-5wt%;
[0026] The molecular weight of the polybenzimidazole is in the range of 60,000 to 220,000.
[0027] further,
[0028] The temperature range for the first stirring and the second stirring is 50 to 90° C.;
[0029] The temperature range of the first oven heating and the second stirring oven heating is 40-120°C.
[0030] further,
[0031] The flat carrier has a flat and smooth surface, such as flat glass, metal plate, high molecular polymer plate or ceramic plate.
[0032] further,
[0033] The thickness of the first thin layer ranges from 100 to 500 microns;
[0034] The thickness of the second thin layer is in the range of 10-100 microns.
[0035] further,
[0036] In the step S1, the mass percentage content of the polyvinylidene fluoride in the first casting solution is 12wt%;
[0037] The molecular weight of the polyvinylidene fluoride is 800,000;
[0038] In the first casting solution, the mass percentage content of zirconium oxide is 5wt%, and the mass percentage content of tert-butylhydroquinone is 0.2wt%;
[0039] In the second casting solution, the mass percentage content of cerium oxide is 0.1wt%, and the mass percentage content of tert-butylhydroquinone is 0.2wt%;
[0040] The mass percentage content of the polybenzimidazole is 3wt%;
[0041] The molecular weight of the polybenzimidazole is 210,000;
[0042] The temperature during the first stirring and the second stirring is 80° C.;
[0043] The temperature of the first oven heating and the second stirring oven heating is 80°C;
[0044] The thickness of the first thin layer is 400 microns;
[0045] The thickness of the second thin layer is 40 micrometers.
[0046] The present invention also provides a proton-conducting composite membrane for a liquid flow battery, which is prepared by adopting the above-mentioned method for preparing the proton-conducting composite membrane for a liquid flow battery.
[0047] Advantages and beneficial results of the method for preparing a proton conducting composite membrane for a flow battery provided by the present invention:
[0048] (1) Through the composite process, the physical advantages of PVDF and PBI are combined to improve the acid resistance, temperature resistance, mechanical strength and other indicators of the composite membrane;
[0049] (2) Through the composite process of film formation, the pore size of the porous membrane is reduced without changing the porosity, effectively reducing the offset of the active material between the positive and negative electrodes, and significantly improving the coulombic efficiency and energy efficiency of the battery;
[0050] (3) Based on the increase in mechanical strength and the reduction in pore size, the thickness of the finished composite membrane is greatly reduced, which effectively reduces the resistance of the composite membrane and significantly improves the voltage efficiency and energy efficiency of the battery;
[0051] (4) The market price of PVDF is relatively low, and the PBI composite layer is thin and uses less material, which reduces the cost of the composite membrane and promotes the market development of liquid flow batteries.
[0052] The proton conducting composite membrane for liquid flow battery provided by the present invention has good selective permeability, can effectively block the migration of positive and negative active materials in liquid flow battery, and greatly improve the coulombic efficiency and stable operation life of liquid flow battery. The present invention has the advantages of low production cost, simple and controllable process flow, stable and reliable membrane performance, and significant improvement of battery efficiency. The technology is easy to scale up for industrialization, and can realize automatic and continuous production, effectively alleviating the problem of high cost and low efficiency of liquid flow battery membranes in the current market.
[0053] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 A flow chart of a method for preparing a proton conducting composite membrane for a flow battery according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. The terms "first", "second", "third", etc. in the specification and claims of this application or the above-mentioned figures are used to distinguish different objects, not to describe a specific order or a primary and secondary relationship. "Multiple" appearing in this application refers to more than two (including two).
[0058] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0059] Figure 1 This is a flow chart of the method for preparing a proton conducting composite membrane for a flow battery provided by the present invention. Figure 1 The method for preparing a proton conducting composite membrane for a flow battery comprises the following steps.
[0060] S1. Dissolve polyvinylidene fluoride and a first modifying additive in a first organic solvent, place the mixture under suitable temperature conditions and stir to obtain a casting liquid A (i.e., a first casting liquid); dissolve polybenzimidazole and a second modifying additive in a second organic solvent, place the mixture under suitable temperature conditions and stir to obtain a casting liquid B (i.e., a second casting liquid).
[0061] The mass percentage content of polyvinylidene fluoride in the casting solution A is in the range of 10wt%-20wt%, preferably 12wt%. When the mass percentage content of polyvinylidene fluoride in the casting solution A is in the above range, the pores and thickness of the film after the casting solution A is formed are appropriate. If the weight percentage concentration of polyvinylidene fluoride in the casting solution A is too small, it is not easy to cast the film. If the weight percentage concentration of polyvinylidene fluoride in the casting solution A is too large, the film thickness is large, which will lead to high film resistance.
[0062] The molecular weight of the polyvinylidene fluoride is 500,000-1,000,000, such as 800,000. The viscosity of the film produced within the molecular weight range is appropriate, which is convenient for factory production.
[0063] The first modifying additive is zirconium oxide and tert-butyl hydroquinone. The second modifying additive is cerium oxide and tert-butyl hydroquinone.
[0064] Among them, in the casting liquid A, the mass percentage content of zirconium oxide is in the range of 3wt%-7wt%, preferably 5wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%, preferably 0.2wt%; in the casting liquid B, the mass percentage content of cerium oxide is in the range of 0.05wt%-0.15wt%, preferably 0.1wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%, preferably 0.2wt%.
[0065] The first organic solvent is dimethyl sulfoxide. The second solvent is N,N-dimethylacetamide, N,N-dimethylformamide, or N-methylpyrrolidone.
[0066] The mass percentage content of the polybenzimidazole is 1wt%-5wt%, preferably 3wt%. When the mass percentage content of the polybenzimidazole in the casting solution B is within the above range, the thickness and resistance of the film after the casting solution B is formed are appropriate. If the weight percentage concentration of the polybenzimidazole in the casting solution B is too small, the film after composite film formation has many defects and it is difficult to form a uniform composite layer. If the weight percentage concentration of the polybenzimidazole in the casting solution B is too large, the composite layer will be too dense, resulting in a high internal resistance of the composite film, while increasing the production cost.
[0067] The molecular weight of the polybenzimidazole is in the range of 60,000 to 220,000, such as 210,000. The viscosity of the film produced within the molecular weight range is appropriate, which is convenient for factory production.
[0068] The suitable temperature, i.e. the stirring temperature, ranges from 50 to 90°C (degrees Celsius), with a preferred value of 80°C.
[0069] The film thickness of the casting solution A is in the range of 100-500 μm (micrometers), with a preferred value of 400 μm.
[0070] S2. Pour the casting liquid A onto the flat surface of the carrier and cast it at a suitable thickness to form a thin layer of the casting liquid A (i.e., the first thin layer). Heat it in an oven at a set temperature until the first thin layer is completely dry to obtain a base film. Coat the casting liquid B on the surface of the prepared base film and cast it at a suitable thickness to form a thin layer of the casting liquid B (i.e., the second thin layer).
[0071] Wherein, the flat carrier includes flat and smooth surface of flat glass, metal plate, polymer plate, ceramic plate.
[0072] The set temperature range is 40-120°C, with a preferred value of 80°C.
[0073] The thickness of the film formed by the casting solution B is in the range of 10-100 μm, with a preferred value of 40 μm.
[0074] S3. At a set temperature, the membrane structure obtained in step S2 is heated in an oven at the set temperature in step S2 until the second thin layer is completely dried to obtain a proton conducting composite membrane.
[0075] The present invention also provides a proton conducting composite membrane, which is prepared by the above-mentioned method for preparing a proton conducting composite membrane for a liquid flow battery. The proton conducting composite membrane can be used in a liquid flow battery, a semi-liquid flow battery, and a fuel cell.
[0076] Embodiment 1:
[0077] A1. Prepare the first casting solution: 10wt% polyvinylidene fluoride, 3wt% zirconium oxide, 0.15wt% tert-butylhydroquinone, and the rest is dimethyl sulfoxide solvent, stir in a water bath or oil bath at 50°C to obtain the first casting solution, i.e., casting solution A, wherein the molecular weight of the polyvinylidene fluoride is 500,000;
[0078] B1. Prepare the second casting solution: PBI 1wt%, cerium oxide 0.05wt%, tert-butylhydroquinone 0.15wt%, and the rest is solvent N,N-dimethylacetamide, and stir them thoroughly in a water bath or oil bath at 50°C to obtain the second casting solution, i.e., casting solution B, wherein the molecular weight of PBI is 60,000, and N,N-dimethylacetamide can be replaced by N,N-dimethylformamide or N-methylpyrrolidone;
[0079] C1. Cast the casting liquid A on a flat and smooth glass plate with a thickness of 100 μm, and place it in a 40°C oven to dry and remove the solvent, that is, to obtain a base film after complete drying. The glass plate can be replaced by a metal plate, a polymer plate, or a ceramic plate;
[0080] D1. Cast the membrane casting liquid B on the base membrane obtained in step c, control the casting thickness to be 10 microns, place it in a 40°C oven to dry and remove the solvent, i.e., completely dry to obtain a composite proton membrane, i.e., a proton conductive composite membrane.
[0081] Embodiment 2:
[0082] A2, prepare the first casting liquid: 12wt% polyvinylidene fluoride, 5wt% zirconium oxide, 0.2wt% tert-butylhydroquinone, and the rest is solvent dimethyl sulfoxide, stir in a water bath or oil bath at 80°C to obtain the first casting liquid, i.e., casting liquid A, wherein the molecular weight of the polyvinylidene fluoride is 800,000;
[0083] B2, prepare the second casting solution: PBI 3wt%, cerium oxide 0.1wt%, tert-butylhydroquinone 0.2wt%, the rest is solvent N, N-dimethylacetamide, stir thoroughly in a water bath or oil bath at 80°C to obtain the second casting solution, i.e., casting solution B, wherein the molecular weight of PBI is 210,000, and N, N-dimethylacetamide can be replaced by N, N-dimethylformamide or N-methylpyrrolidone;
[0084] C2, casting liquid A on a glass plate with a thickness of 400 microns, placing it in an oven at 80°C to dry and remove the solvent, that is, to completely dry the base film, wherein the glass plate can be replaced by a metal plate, a polymer plate, or a ceramic plate;
[0085] D2. Cast the membrane casting liquid B on the base membrane obtained in step c, control the casting thickness to be 40 microns, place it in an oven at 80°C to dry and remove the solvent, i.e., completely dry to obtain a composite proton membrane, i.e., a proton conducting composite membrane.
[0086] Embodiment 3:
[0087] A3, prepare the first casting liquid: 20wt% polyvinylidene fluoride, 7wt% zirconium oxide, 0.25wt% tert-butylhydroquinone, and the rest is solvent dimethyl sulfoxide, stir in a water bath or oil bath at 90°C to obtain the first casting liquid, i.e., casting liquid A, wherein the molecular weight of the polyvinylidene fluoride is 1 million;
[0088] B3, according to PBI 5wt%, cerium oxide 0.15wt%, tert-butylhydroquinone 0.25wt%, the rest is solvent N, N-dimethylacetamide, fully stirred in a water bath or oil bath at 90°C to obtain the second casting liquid, i.e., casting liquid B, wherein the molecular weight of PBI is 220,000, and N, N-dimethylacetamide can be replaced by N, N-dimethylformamide or N-methylpyrrolidone;
[0089] C3, casting liquid A on a glass plate with a thickness of 500 μm, placing it in a 120°C oven to dry and remove the solvent, i.e. completely dry to form a base film, wherein the glass plate can be replaced by a metal plate, a polymer plate, or a ceramic plate;
[0090] D3. Cast the membrane casting liquid B on the base membrane obtained in step c, control the casting thickness to be 100 microns, place it in a 120°C oven to dry and remove the solvent, i.e., completely dry to obtain a composite proton membrane, i.e., a proton conductive composite membrane.
[0091] The proton conducting composite membrane for liquid flow battery provided by the present invention has good selective permeability, can effectively block the migration of positive and negative active materials in liquid flow battery, and greatly improve the coulombic efficiency and stable operation life of liquid flow battery. The present invention has the advantages of low production cost, simple and controllable process flow, stable and reliable membrane performance, and significant improvement of battery efficiency. The technical industrialization is easy to scale up, and automatic and continuous production can be realized, effectively alleviating the problem of high cost and low efficiency of liquid flow battery membranes in the current market.
[0092] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a proton conducting composite membrane for a flow battery, characterized in that: Includes steps: S1, dissolving polyvinylidene fluoride and a first modifying additive in a first organic solvent, and performing a first stirring to obtain a first casting solution; dissolving polybenzimidazole and a second modifying additive in a second organic solvent, and performing a second stirring to obtain a second casting solution; S2, coating the first casting liquid on a flat support surface to form a first thin layer by casting, performing a first oven heating until the first thin layer is completely dried to obtain a base film, and then coating the second casting liquid on the surface of the base film to form a second thin layer by casting; S3, heating the membrane structure obtained in step S2 in an oven for a second time until the second thin layer is completely dry, thereby preparing a proton conducting composite membrane.
2. The method for preparing a proton conducting composite membrane for a flow battery according to claim 1, characterized in that: In the step S1, the mass percentage content of the polyvinylidene fluoride in the first casting solution is in the range of 10wt%-20wt%; The molecular weight of the polyvinylidene fluoride is 500,000-1,000,000.
3. The method for preparing a proton conducting composite membrane for a flow battery according to claim 2, characterized in that: The first modifying additive is zirconium oxide and tert-butyl hydroquinone; The second modification additive is cerium oxide and tert-butyl hydroquinone; In the first casting solution, the mass percentage content of zirconium oxide is in the range of 3wt%-7wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%; In the second casting solution, the mass percentage content of cerium oxide is in the range of 0.05wt%-0.15wt%, and the mass percentage content of tert-butylhydroquinone is in the range of 0.15wt%-0.25wt%.
4. The method for preparing a proton conducting composite membrane for a flow battery according to claim 3, characterized in that: The first organic solvent is dimethyl sulfoxide; The second solvent is N,N-dimethylacetamide, N,N-dimethylformamide, or N-methylpyrrolidone.
5. The method for preparing a proton conducting composite membrane for a flow battery according to claim 4, characterized in that: The mass percentage content of the polybenzimidazole is 1wt%-5wt%; The molecular weight of the polybenzimidazole is in the range of 60,000 to 220,000.
6. The method for preparing a proton conducting composite membrane for a flow battery according to claim 5, characterized in that: The temperature range for the first stirring and the second stirring is 50 to 90° C.; The temperature range of the first oven heating and the second stirring oven heating is 40-120°C.
7. The method for preparing a proton conducting composite membrane for a flow battery according to claim 6, characterized in that: The flat carrier has a flat and smooth surface, such as flat glass, metal plate, high molecular polymer plate or ceramic plate.
8. The method for preparing a proton conducting composite membrane for a flow battery according to claim 7, characterized in that: The thickness of the first thin layer ranges from 100 to 500 microns; The thickness of the second thin layer is in the range of 10-100 microns.
9. The method for preparing a proton conducting composite membrane for a flow battery according to claim 8, characterized in that: In the step S1, the mass percentage content of the polyvinylidene fluoride in the first casting solution is 12wt%; The molecular weight of the polyvinylidene fluoride is 800,000; In the first casting solution, the mass percentage content of zirconium oxide is 5wt%, and the mass percentage content of tert-butylhydroquinone is 0.2wt%; In the second casting solution, the mass percentage content of cerium oxide is 0.1wt%, and the mass percentage content of tert-butylhydroquinone is 0.2wt%; The mass percentage content of the polybenzimidazole is 3wt%; The molecular weight of the polybenzimidazole is 210,000; The temperature during the first stirring and the second stirring is 80° C.; The temperature of the first oven heating and the second stirring oven heating is 80°C; The thickness of the first thin layer is 400 microns; The thickness of the second thin layer is 40 micrometers.
10. A proton conducting composite membrane for a liquid flow battery, characterized in that: The proton conducting composite membrane is prepared by the method for preparing a proton conducting composite membrane for a flow battery according to any one of claims 1 to 9.